The Polish Vision of EU Future: Imitation of the Hungarian Model? - Tosiek, Piotr (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2019)
The argument of this article is based on the assumption that the Hungarian EU model and the imitative Polish EU vision are based on Euroscepticism, creating the concepts equally incompatible with Western standards of democracy and the EU mainstream views. The strong articulation of extreme opinions leads to the isolation, while in the light of liberal intergovernmentalism it is the Polish concept that undermines the relative position of that state in the EU system more than the Hungarian one. First, compared with Hungary, Poland has completely different interests based on a Russian threat and geographical location. Second, due to its size Poland could be a relatively strong player in the EU, while presentation of a radical concept weakens its role, making it impossible to act as intermediary, an honest broker or a group leader. On the contrary, the Hungarian model, based on a similar concept but applied to a small political actor, can strengthen the relatively marginal position of that state, being a beneficial way to achieve some goals in tactical games.

Argumentacja niniejszego artykułu opiera się na założeniu, że proponowany przez Węgry model funkcjonowania UE i imitująca go polska wizja Unii opierają się na eurosceptycyzmie i są koncepcjami równie nieprzystającymi do zachodnich standardów demokracji i poglądów dominujących w UE. Silna artykulacja skrajnych opinii prowadzi do izolacji, podczas gdy w świetle liberalnej międzyrządowości polska koncepcja podważa względną pozycję tego państwa w systemie UE bardziej niż węgierska. W porównaniu z Węgrami Polska ma bowiem zupełnie inne interesy oparte na zagrożeniu ze strony Rosji oraz położeniu geograficznym. Ponadto, ze względu na swoją wielkość, Polska może być stosunkowo silnym graczem w UE, a prezentacja radykalnej koncepcji osłabia jej rolę, czyniąc niemożliwym odgrywanie roli mediatora, uczciwego pośrednika lub lidera grupowego. W przeciwieństwie do tego model węgierski, oparty na podobnej koncepcji, ale stosowany przez niewielkiego aktora politycznego, może wzmocnić relatywnie marginalną pozycję tego państwa i być korzystnym sposobem osiągania niektórych celów w grach taktycznych.
Polska wizja przyszłości UE: imitacja modelu węgierskiego?
Keywords: Hungary; Poland; European Union; Euroscepticism; illiberal democracy; Węgry; Polska; Unia Europejska; eurosceptycyzm; demokracja nieliberalna